Pelatihan Diklat Pemanfaatan Aplikasi Online Menggunakan Cek Plagiarisme Dengan Turnitin Untuk Guru Dan Dosen Pada Perkumpulan Profesi Multimedia Dan Teknologi Informasi (PPMULTINDO) - Rakasiwi, Sindhu; Marjuni, Aris; Rijati, Nova; Himawan, Heribertus; Jatmoko , Cahaya; Sinaga, Daurat (Community : Jurnal Pengabdian Pada Masyarakat, 2024)
Conveying appropriate information to be understood quickly and accurately is very important in various areas of life, both academic and non-academic. A teacher or lecturer is a teacher whose job is to educate and provide instruction to students or students. Data visualization is one way that can be used to present data. The advantage of this method is the availability of statistical graphics which can enrich the display of information so that the results are more interactive for the audience. Google Data Studio is an application launched by Google that can be used to convert raw data into interesting and strategic information for users. That way, the information becomes more appropriate to understand quickly and accurately.